The Detection of Calcium and Sodium Using Green Algae Spirogyra - Wong, Ling Shing; Kiew, Wen Yi (2016)
Continuous monitoring of metals is necessary due to the influx of metals into the environment from human activities. The presence of green algae Spirogyra in various water bodies can be used as an effective bioindicator for the detection of metals. In this paper, naturally available pigments in Spirogyra- chlorophylls and carotenoids were used to detect the presence of light metals by measuring the light absorbance at λ = 663 nm and 450 nm respectively, before and after the exposure to Ca and Na. The results showed both markers were sensitive to the presence of Ca and Na in aqueous environment, with carotenoids gave a better response. As all markers showed high correlation to the concentration of metals within 0.001 mg/L - 0.100 mg/L, Spirogyra had great potential to be as bioindicator for Ca and Na in aqueous environment.